Secondary education and employment in Trinidad and Tobago: Implications for educational planning - Dottin, Ambrose Cornelius (1973)
This study was designed to investigate the relationship between the development of secondary education and the employment of the products of the system. The opinions of Form V and Form VI (Upper) students from the 45 public secondary schools in Trinidad and Tobago, and the school principals, together with the opinions of 10 major employers in the private sector, provided the data for the study. The cohort of students consisted of a sample of one randomly selected Form V, and the entire Upper VI enrollment of the schools. The major findings of the study were: 1) secondary school students manifested very high vocational aspirations and expectations, on a scale which raised serious doubts about their intellectual and financial capacity to realize their goals; 2) secondary education is geared to, and perceived as, preparation for higher education rather than immediate employment; 3) students, principals, and employers felt that the secondary school system needed to be reoriented to facilitate the employment of school leavers; and 4) males showed distinctly higher aspirations and expectations than females
Keywords: Secondary education